(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of this paper is to present the fluctuations of emery mining, from Ancient times to the present day, in the island of Naxos, Greece. Many Aegean islands were characterised in Antiquity by intense mining and quarrying activities, and many such activities continue even today. Emery is along with marble, the distinctive industrial mineral of the Cyclades, even now that production has largely ceased. This is an analysis of how emery came to be in Naxos, and how its existence and its exploitation by the local population shaped the society, the economy and the folklore of the local mining communities. In addition, since such mineral wealth is a matter not only of local but of national importance as well, the significance of emery export in Greek national economy will be discussed, along with how the changing international industrial and financial reality affected mining and thus the life of the locals. While presently profitable emery mining is rather unlikely, it is still possible for the insular community and economy to benefit from the establishment of a thematic geopark, based on the existing mines and the old mining infrastructure.